Auditory brainstem response: an overview of neurophysiological implications and clinical applications - Syed Hamid Habib; Syed Shahid Habib (Journal of the Pakistan Medical Association, 2021)
Evoked Potentials are electrical potentials that occur in a group of neurons in response to stimulation of a sensory organ which can be recorded by surface electrodes. Testing evoked potentials is useful in assessing the integrity of neuronal pathways both at sensory and motor levels of neural control. Early auditory evoked potentials include cochlear and brainstem auditory-evoked potentials, popularly known as electrocochleogram, and auditory brainstem response. Evoked potential audiometry is a neurophysiogical test to assess auditory pathway function in response to auditory stimuli. Auditory brainstem response mainly assesses brainstem functions and integrity. These evoked potentials are widely used for assessment of the cochlear functions, auditory nerve and the brainstem. Most common indications for auditory evoked potentials include routine newborn hearing screening for auditory pathway deficits, detecting retrocochlear pathologies, intraoperative and intensive care monitoring, frequency-related measurement of auditory sensitivity and for diagnosing some demyelinating disorders in initial stages. Continuous...